2013
DOI: 10.1002/jbm.a.34791
|View full text |Cite
|
Sign up to set email alerts
|

Tuning scaffold mechanics by laminating native extracellular matrix membranes and effects on early cellular remodeling

Abstract: At approximately 50 μm thin, the human amniotic membrane (hAM) has been shown to be a versatile biomaterial with applications ranging from ocular transplants to skin and nerve regeneration. These investigations describe laminating layers of the hAM into a multilayered, conformation creating a thicker, more robust biomaterial for applications requiring more supportive structures. Amniotic membranes were decellularized using 4 M NaCl and prepared as either flat single-layered sheets or rolled into concentric fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…As mentioned, the finite element model proposed only predicts the low-strain region of the stress-strain curve (linear elastic region). In some tissue engineering applications, such as nerve and skin regeneration, the linear, low-strain region of the stress-strain curve was used to calculate the elastic modulus of samples and considered to represent physiological behavior in the human vasculature (Amensag and McFetridge, 2014). In a similar study, isotropic linear elastic behavior was reported and 10% strain used to calculate the elastic modulus of scaffolds fabricated as cardiac-mimetic structures; furthermore, 10 to 25% strain was reported as the cardiac-relevant strain range in physiological conditions (Neal et al, 2012).…”
Section: Effect Of Crosslinker Volumementioning
confidence: 99%
“…As mentioned, the finite element model proposed only predicts the low-strain region of the stress-strain curve (linear elastic region). In some tissue engineering applications, such as nerve and skin regeneration, the linear, low-strain region of the stress-strain curve was used to calculate the elastic modulus of samples and considered to represent physiological behavior in the human vasculature (Amensag and McFetridge, 2014). In a similar study, isotropic linear elastic behavior was reported and 10% strain used to calculate the elastic modulus of scaffolds fabricated as cardiac-mimetic structures; furthermore, 10 to 25% strain was reported as the cardiac-relevant strain range in physiological conditions (Neal et al, 2012).…”
Section: Effect Of Crosslinker Volumementioning
confidence: 99%
“…Indeed, scaffolding materials may present a biomimetic structure of different extracellular matrix (ECM) components that could stimulate cell survival and differentiation [27,30]. It is however essential to optimize biological [31], mechanical [32,33] and physicochemical properties [34] of scaffolding material before they can be successfully employed. In brain tissue engineering, the size of the scaffold is one of the most crucial issues as it has to be small enough to be injectable into the site of lesion in deep brain [1,27].…”
Section: Introductionmentioning
confidence: 99%
“…[34,48] Placental derived matrix has been shown to induce angiogenesis. [15] Bottom left represents capillaries formed in vitro on human placental matrix coated TC plate.…”
Section: Figurementioning
confidence: 99%